Keputusan Investasi Dengan Metode Capital Asset Pricing Model (CAPM) Pada Perusahaan LQ45 Rentan Waktu 2020 - 2024 - Ningsih, Ida Wahyu; Basworo, Fajar Hanung; Susilowati, Indah (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study explores how risk relates to return in the context of LQ45 index stocks for the period 2020–2024, using the Capital Asset Pricing Model (CAPM) as the main analytical tool. CAPM helps estimate a stock's expected return by factoring in its systematic risk, represented by beta. The research applies a quantitative descriptive approach, with 24 selected companies meeting specific criteria. The analysis confirms a clear positive relationship between beta and expected return—stocks with higher risk tend to offer higher potential returns. To provide deeper insight, the study also compares actual stock returns to their expected returns based on CAPM, allowing for classification into undervalued and overvalued categories. The findings indicate that six stocks are undervalued, offering potential opportunities for investors, while the remaining eighteen are overvalued. These results highlight how CAPM can be used not only to understand risk-return dynamics but also to support more informed and strategic investment decisions in the capital market.